Measuring The Levels of Perfectionism Among Muslim Gifted and Talented Students - Zainal, Rosita; Faridilatras, Faiqah Atiyyah; Megat Nazaruddin, Puteri Farrah Najeehah; Rosdi, Nursyamilah; Abd Razak, Amnah Zanariah (‘Abqari Journal, 2024)
In Psychology, perfectionism is a broad personality trait characterized by a person’s concern with striving for flawlessness and try to be the best in every field the venture into. The main purpose of this study is to identify the levels of perfectionism among gifted and talented Muslim students at PERMATA Insan College (KPI). This study is important to avoid the negative effect of perfectionism among students because some studies conducted with gifted students have revealed that perfectionism breeds harsh self-criticism, self-doubt, and a fear of failure, all of which are associated with an increased propensity for suicidal thoughts and actions. The level of perfectionism are determined with the assistance of Frost Multidimensional Perfectionism Scale by Frost (1990). There are low, medium and high-level perfectionists. Previous studies have proven several factors that influence the levels of perfectionism such as surroundings and other people's expectations. The scale consists of 35 questions which contain six constructs. 83 students has taken part in this study. This quantitative study shows that majority of PERMATA Insan College’s students perfectionism level is at medium-level. Some suggestions were made to get a better understanding and help students with perfectionism and at the same time increase their level of thinking styles in the quest of producing future gifted and talented Islamic scholar.